Ultrasoft state of microquasar Cygnus X-3: X-ray polarimetry reveals the geometry of the astronomical puzzle - Veledina, Alexandra; Poutanen, Juri; Bocharova, Anastasiia; Di Marco, Alessandro; Forsblom, Sofia V.; La Monaca, Fabio; Podgorný, Jakub; Tsygankov, Sergey S.; Zdziarski, Andrzej A.; Ahlberg, Varpu; Green, David A.; Muleri, Fabio; et al. (EDP Sciences, 2025)
Cygnus X-3 is an enigmatic X-ray binary that is both an exceptional accreting system and a cornerstone for population synthesis studies. Prominent X-ray and radio properties follow a well-defined pattern, and yet the physical reasons for the state changes observed in this system are not known. Recently, the presence of an optically thick envelope around the central source in the hard state was revealed using the X-ray polarization data obtained with the Imaging X-ray Polarimetry Explorer (IXPE). In this work we analyse IXPE data obtained in the ultrasoft (radio quenched) state of the source. The average polarization degree (PD) of 11.9 ± 0.5% at a polarization angle (PA) of 94° ±1° is inconsistent with the simple geometry of the accretion disc viewed at an intermediate inclination. The high PD, the blackbody-like spectrum, and the weakness of fluorescent iron line imply that the central source is hidden behind the optically thick outflow, similar to the hard-state geometry, and its beamed radiation is scattered, by the matter located along the funnel axis, towards our line of sight. In this picture the observed PD is directly related to the source inclination, which we conservatively determine to lie in the range 26° < i < 28°. Using the new polarimetric properties, we propose a scenario that can be responsible for the cyclic behaviour of the state changes in the binary.